Postnatal serum creatinine is elevated in preterm infants with PPROM-induced anhydramnios - Nora Bruns; Ann-Christin Stähling; Sandra Greve; Christel Weiss; Angela Köninger; Ursula Felderhoff-Müser; Hanna Müller (Elsevier, 2020)
Background: The reason for increased serum creatinine levels in preterm infants often remains unclear. We aimed to determine whether postnatal serum creatinine in preterm infants correlates with intake of amniotic fluid, represented by the amount of amniotic fluid after preterm premature rupture of membranes (PPROM). Methods: 74 preterm infants with PPROM > 48 h duration were retrospectively studied. Postnatal creatinine concentration was determined at day 2-5, 10-17 and 26-33 of life and compared between infants with normal intrauterine amniotic volumes, oligohydramnios and anhydramnios. Results: Mean gestational age of included patients was 29.7 weeks (range: 24.0-36.1 weeks) and mean birth weight was 1452 g (range: 560-2940 g). Serum creatinine concentration was similar at day 2-5 and day 10-17 of life between the three groups. We observed a significant decrease in creatinine concentration from day 2-5 to day 26-33 in infants with normal amniotic fluid volume and oligohydramnios (p = 0.0001 and p = 0.0071, respectively), but not in anhydramnios. On day 26-33 of life, infants with anhydramnios showed significantly higher creatinine levels compared to infants with normal amniotic fluid volume and oligohydramnios (p = 0.0211). Conclusion: Postnatal serum creatinine of preterm infants at day 26-33 of life is elevated in infants with PPROM-induced anhydramnios, but not in oligohydramnios.